PHYSICOCHEMICAL AND MICROBIOLOGICAL CHARACTERIZATION OF WWTP AND DT SLUDGE UNDER AGRONOMIC RE-USE APPROACH - Candela Levano, Gianella M. (2025)
The objective of the study was to evaluate the agronomic potential of WWTP and DT sludge produced in Peru. For this, different aerobic and anaerobic wastewater treatment technologies were selected, as well as on-site sanitation systems in the cities of Lima, Ayacucho, Arequipa and Cusco. The aerobic technologies evaluated were: conventional aeration activated sludge, extended aeration, ICEAS and aerated lagoon. Regarding the anaerobic technologies, the following were selected: anaerobic lagoon, anaerobic digester and Imhoff tank. The on-site sanitation systems chosen were those with weekly, monthly and annual storage chambers. The sampled sludge was characterized physicochemically and microbiologically according to DS-N°015-2017-VIVIENDA, which determines whether a sludge can be reused and classified as type A or B biosolids. Type A biosolids are applicable to the soil without sanitary restrictions. while those of type B have restrictions depending on the location of the soil and/or type of crop. The concentrations of C, N, P and K in the sludge were analyzed to evaluate their possible agronomic reuse. It was found that extended aeration sludge, aerated lagoon, anaerobic lagoon, anaerobic digester and Imhoff tank have characteristics similar to those of type B biosolids and have adequate agronomic potential due to their content of organic matter and nutrients. On the other hand, conventional aeration sludge, ICEAS and BES require stabilization processes to be reused.